Evaluation of the fresh and mechanical properties of nano-engineered self compacting concrete containing graphite nano/micro platelets. (December 2022) - Tufail, Rana Faisal; Naeem, Muhammad Harris; Ahmad, Jawad; Waheed, Hafiz; Majdi, Ali; Farooq, Danish; Maqsoom, Ahsen; Butt, Faheem
Abstract: The graphite nano/micro platelets (GNMPs) offer distinct features for the effective reinforcement of cementitious matrices in the behaviors of concrete. The thoroughly dispersed and well-bonded nanomaterials provide effective control of the size and propagation of defects (microcracks) in the matrix and also act as closely spaced barriers against diffusion of moisture and aggressive solutions into the concrete. Graphite nanomaterials can play multi-faceted roles in enhancing the mechanical and physical attributes of concrete materials. The GNMPs have to exhibit enhanced mechanical and other functionalities to be suitable for emerging structural applications. Although GNMPs improved some of the mechanical performance of concrete but less information is available particular the influence of (GNMPs) in self-compacting concrete (SSC). Therefore, in this research an innovative nano-engineered self-compacting concrete was prepared using 0.1%, 0.2%, 0.3%, 0.4% and 0.5% GNMPs. The rheological properties were assessed through slump flow, v funnel, v funnel at T5 minute, L box test while mechanical performance was assessed through compressive and tensile tests. The microstructural properties of the self-compacting concrete (SSC) with GNMPs were investigated through Scanning Electron Microscopy (SEM). The results indicate that the filling and passing ability of SCC improved with GNMPs. Furthermore, 0.3% addition of GNMPs shows 42% and 21.3% enhancement in compressive and tensile strength as compared to reference concrete respectively. Overall, the study demonstrated the effectiveness of GNMPs in SCC and may be applied in practical structural engineering applications.